Cecum microbiome and metabolism characteristics of Silky Fowl and White Leghorn chicken in late laying stages - Yang, Xue; Tai, Yurong; Ma, Yuhao; Xu, Zihan; Hao, Jiaqi; Han, Deping; Li, Junying; Deng, Xuemei (Frontiers in Microbiology, 2022)
Cecal microflora plays a key role in the production performance and immune function of chickens. White Leghorn (WL) is a well-known commercial layer line chicken with high egg production rate. In contrast, Silky Fowl (SF), a Chinese native chicken variety, has a low egg production rate, but good immune performance. This study analyzed the composition of cecal microbiota, metabolism, and gene expression in intestinal tissue of these varieties and the correlations among them. Significant differences were observed in the cecal microbes: Bacteroides was significantly enriched in WL, whereas Veillonellaceae and Parabacteroides were significantly enriched in SF. Carbohydrate biosynthesis and metabolism pathways were significantly upregulated in WL cecum, which might provide more energy to the host, leading to persistently high levels of egg production. The higher Parabacteroides abundance in SF increased volicitin content, enhanced α-linolenic acid metabolism, and significantly negatively correlated with metabolites of propanoate metabolism and carbohydrate metabolism. Genes related to lipid metabolism, immunity, and melanogenesis were significantly upregulated in the SF cecum, regulating lipid metabolism and participating in the immune response, while genes related to glucose metabolism and bile acid metabolism were expressed at higher levels in WL, benefiting energy support. This study provided a mechanism for intestinal microorganisms and metabolic pathways to regulate chicken egg-laying performance and immunity.